Cost-effectiveness of Kang Ai injection plus chemotherapy vs. Shenqi Fuzheng injection plus chemotherapy in the first-line treatment of advanced non-small cell lung cancer - Zhu, Junjie; Tian, Lei (Frontiers in Medicine, 2024)
Objective: This study aimed to evaluate the cost-effectiveness of two Chinese patent medicines, including Kang Ai injection and Shenqi Fuzheng injection with each combined with platinum-based chemotherapy as the first-line treatment for patients with advanced non-small cell lung cancer (NSCLC) in China. Methods: From Chinese healthcare system perspective, a three state Markov model with a cycle of three weeks and a ten-year horizon was constructed to derive the incremental cost-effectiveness ratio (ICER). Since only individual patient data of progression-free survival of Kang Ai injection group can be obtained, we extrapolated median overall survival (mOS) of Kang AI injection group and median progression-free survival (mPFS) and mOS of Shenqi Fuzheng injection group based on published literature and methods. Then survival curves were estimated by the method of declining exponential approximation of life expectancy (DEALE), which is based on the assumption that survival follows a declining exponential function. We performed one-way sensitivity analysis and probabilistic sensitivity analysis to test the robustness. Additionally, a scenario analysis was adopted to investigate the impact of using best-fitting distribution for progression-free survival (PFS) curve of Kang Ai injection group on the economic conclusion. Results: The base-case result indicated that Kang Ai injection group provided 0.217 incremental quality-adjusted life years (QALYs) at an incremental cost of 103.38 compared with Shenqi Fuzheng injection group. The incremental cost-effectiveness ratio (ICER) was 476.41/QALY, which was much lower than the willingness to pay threshold of one time the GDP per capita of China in 2022 (12,070/QALY). Deterministic sensitivity analysis result showed that ICER was most sensitive to the changes in odds ratio (OR) value. The probabilistic sensitivity analysis confirmed the robustness of base-case analysis results. The scenario analysis result showed that by using Log-Normal distribution to fit the PFS curve of Kang Ai injection group and shortening the time horizon to five years, the ICER was 4,081.83/QALY, which was still much lower than the willingness to pay threshold. Conclusion: Kang Ai injection combined with platinum-based chemotherapy appeared to be more cost-effective for the treatment of advanced NSCLC than Shenqi Fuzheng injection combined with platinum-based chemotherapy.